ANALISIS MODAL SOSIAL UPACARA PENANAMAN BANGKA DI DUSUN EMPAONG DESA TINTING BOYOK KECAMATAN SEKADAU HULU KABUPATEN SEKADAU - Ayu Werna Yanti; F. Y. Khosmas; Hadi Wiyono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis paper presents an analysis about social capital of Penanaman Bangkaceremony at Empaong Hamlet, Tinting Boyok village, Sekadau Hulu District,Sekadau regency. This research aims to determine social capital that exists incommunity of Empaong Hamlet, Tinting Boyok village, Sekadau HuluDistrict, Sekadau regency during Penanaman Bangka ceremony. Thisresearch used qualitative descriptive method using field observation,interview with local community, and documentation. Source of the data thatare used by the researcher were primary data and secondary data. Dataprocessing techniques obtained through three stages, namely: data reduction,data presentation, and making conclusions on the research finding. Thefinding of the research showed: 1) social capital in the community a duringPenanaman Bangka Ceremony, the role of social capital in the PenanamanBanka Ceremony, factors that influence social capital during PenanamanBangka Ceremony. 2) Forms of social capital in community duringPenanaman Bangka ceremony in Empaong Hamlet, Tinting Boyok village,Sekadau Hulu District, Sekadau regency. 3) The values of facilities and stagesin Penanaman Bangka ceremony in Empaong Hamlet, Tinting Boyok village,Sekadau Hulu District, Sekadau regency.Keywords: Social capital, forms of social capital, Penanaman Bangkaceremony.